Prevalence and the factors associated with oral anticoagulant use among nursing home residents. (31st August 2021) - Chen, Qiaoxi; Lapane, Kate; Nunes, Anthony P.; Tjia, Jennifer; Hugunin, Julie; Alcusky, Matthew
Abstract: What is Known and Objective: Anticoagulants are indicated for treatment and prevention of several clinical conditions. Prior studies have examined anticoagulant utilization for specific indications and in community‐dwelling populations. Decision‐making regarding anticoagulant prescribing in the nursing home setting is particularly challenging because advanced age and clinical complexity places most residents at increased risk for adverse drug events. To estimate the prevalence of oral anticoagulant (OAC) use (overall, warfarin, direct oral anticoagulants (DOACs)) and identify factors associated with oral anticoagulant use among the general population of residents living in nursing homes. Methods: This point prevalence study was conducted among 506, 482 residents in US nursing homes on 31 October 2016 who were enrolled in Medicare fee‐for‐service. Covariates including demographics, clinical conditions, medications, cognitive impairment and functional status were obtained from Minimum Data Set 3.0 assessments and Medicare Part A and D claims. Oral anticoagulant use was identified using dispensing dates and days supply information from Medicare Part D claims. Robust Poisson models estimated adjusted prevalence ratios (aPR) for associations between covariates and 1) any anticoagulant use, and 2) DOAC versus warfarin use. Results and Discussion: Overall, 11.8% of residents used oral anticoagulants. Among users, 44.3% used DOACs. Residents with body mass index (BMI) ≥40 kg/m 2 (aPR: 1.66; 95% CI: 1.61 −1.71), with functional dependency in activities of daily living, polypharmacy and higher CHA2 DS2 ‐VASc risk ischaemic stroke scores, had a higher prevalence of oral anticoagulant use. Women (aPR: 0.78; 95% CI: 0.76–0.79), residents with limited life expectancy (aPR 0.80; 95% CI: 0.76–0.83), those with moderate‐to‐severe cognitive impairment (aPR: 0.67; 95% CI: 0.65–0.68), those using NSAIDs or antiplatelets, and non‐white racial/ethnic groups had a lower prevalence of anticoagulant use. Residents with higher levels of polypharmacy, BMI and age had a lower prevalence of DOAC use (versus warfarin). What is New and Conclusion: Approximately one in eight general nursing home residents use oral anticoagulants and among oral anticoagulant users, only slightly more residents used warfarin than DOACs. The lower prevalence of anticoagulation among women and non‐white racial/ethnic groups raises concerns of potential inequities in quality of care. Lower oral anticoagulant use among residents with limited life expectancy suggests possible deprescribing at the end of life. Further research is needed to inform resident‐centred shared decision‐making that explicitly considers treatment goals and individual‐specific risks and benefits of anticoagulation at all stages of the medication use continuum.